Industry 4.0 and last mile logistics, new challenges and approaches: a bibliometric review - Jacay Aldui, Diego Jair (2023)
Discussions about the relationship between the fourth industrial revolution, also called Industry 4.0, and last mile logistics are an issue that has grown over time due to the development of new technologies that take on new industries and the lack of processes and innovation to accompany the evolution of Industry 4.0 and cover optimization needs in the last mile of the logistics chain. This article's main objective is to research the new challenges and approaches that arise in this fourth industrial revolution to face and optimize the last mile of the logistics chain. To fulfill this purpose, a systematic literature review was carried out, as well as a bibliometric analysis. 100 articles were reviewed in detail, the origin of these articles is 100% Scopus to ensure quality content in the research. The results show a constant development of the technologies that make up Industry 4.0 in organizations worldwide, which leads to large-scale growth, thus resulting in the need for process optimization for last-mile logistics.